Comparing the Effect of Single Anastomosis Sleeve- Jejunal Bypass and Sleeve Gastrectomy on Weight Loss and Metabolic Comorbidities among Patients with Morbid Obesity - Seyed Vahid Hosseini; Ibrahim Jaweek; Neda Haghighat; Mohammad Mostafa Safarpour; Shima Sakhti; Nader Moeinvaziri (International Journal of Nutrition Sciences)
Background: The rise in morbid obesity has prompted the development of new bariatric surgery techniques, including the Single Anastomosis Sleeve Jejunal Bypass (SASJ). This study aimed to compare the effects of SASJ and conventional Sleeve Gastrectomy (SG) on weight loss, biochemical markers, and comorbidities and to provide essential insightsfor tailored interventions.Methods: In a multicenteric observational-analytical retrospective cohort study from January 2019 to January 2024 at Faghihi, Mother and Child and Abou Ali Sina hospitals in Shiraz, Southern Iran; 61 patients (32 underwent SASJ and 29 underwent SG) were enrolled to assess weight, anthropometric indices, lipid profile and metabolic outcome.Results: Both SASJ and SG groups showed significant reductions in mean body mass index (BMI) (p<0.001); a significant decrease in mean waist circumference [SASJ from 115.76±11.72 to 84.12±12.87 (p<0.001); SG from 126.68±10.44 to 98.95±11.37 (p<0.001)]. Significant improvements were noted in triglycerides and HDL cholesterol levels among both groups, while the SASJ group showed changes in LDL cholesterol too. Both SASJ and SG groups demonstrated a significant improvement in patients withtype II diabetes mellitus (p=0.017 and p=0.046, respectively).Conclusion: Both procedures significantly could reduce weight and improve comorbidities; however, SASJ was shown to have more benefits, especially in reduction of waist circumference and improvement of lipid profile.